On impulsive Sturm - Liouville operators with singularity and spectral parameter in boundary conditions - Amirov, R. Kh.; Güldü, Y.; Topsakal, N. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study properties and the asymptotic behavior of spectral characteristics for a class of singular Sturm-Liouville differential operators with discontinuity conditions and an eigenparameter in boundary conditions. We also determine the Weyl function for this problem and prove uniqueness theorems for a solution of the inverse problem corresponding to this function and spectral data.